2023
DOI: 10.1186/s12889-023-15870-x
|View full text |Cite
|
Sign up to set email alerts
|

Sleep disorder, Mediterranean diet, and all-cause and cause-specific mortality: a prospective cohort study

Abstract: Background There is a bidirectional effect between sleep disorders and Mediterranean diet (MED), but the joint effect of MED and sleep disorders on mortality is unclear. The aim of this study was to investigate whether there is a synergistic effect of adherence to MED and sleep disorders on all-cause and cause-specific mortality. Methods The study included 23,212 individuals in the National Health and Nutrition Examination Survey (NHANES) from 2005… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 63 publications
0
3
0
Order By: Relevance
“…It should be mentioned that the relationship between the adherence to the MD along with sleep habits and CVD is rarely explored. Recently, in the National Health and Nutrition Examination Survey (NHANES), it was found that lower adherence to a MD and sleep disorders synergistically increased all-cause and CVD mortality [ 21 ]. This study seems to be in line with our observation that sleep duration modifies the association between adherence to the MD and CVD risk.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It should be mentioned that the relationship between the adherence to the MD along with sleep habits and CVD is rarely explored. Recently, in the National Health and Nutrition Examination Survey (NHANES), it was found that lower adherence to a MD and sleep disorders synergistically increased all-cause and CVD mortality [ 21 ]. This study seems to be in line with our observation that sleep duration modifies the association between adherence to the MD and CVD risk.…”
Section: Discussionmentioning
confidence: 99%
“…Sleep disorders such as sleep apnea have been associated with increased CVD risk [ 20 ]. To the best of our knowledge, the relation among MD, sleep and CVD risk has been studied in only one previous study, by Wang et al, in which they evaluated 23,212 individuals from the National Health and Nutrition Examination Survey (NHANES), and found that lower adherence to a MD in the presence of sleep disorders synergistically increase all-cause and CVD mortality [ 21 ]. However, it should be clarified that this study examined only sleep disorders, and not normal sleep habits, in relation to mortality (i.e., all-cause and CVD mortality).…”
Section: Introductionmentioning
confidence: 99%
“…Current treatment options include non-pharmacological and pharmacological treatments (including melatonin, antipsychotic medication, antidepressants, α−adrenergic agonists, and sedative-hypnotic drugs) [ 3 ]. It is worth noting that the impact of dietary factors, including milk on sleep disorders, have received substantial attention [ 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%